2018
DOI: 10.1051/0004-6361/201833329
|View full text |Cite
|
Sign up to set email alerts
|

Improving Hickson-like compact group finders in redshift surveys: an implementation in the SDSS

Abstract: Aims. In this work we present an algorithm to identify compact groups (CGs) that closely follows Hickson's original aim and that improves the completeness of the samples of compact groups obtained from redshift surveys. Methods. Instead of identifying CGs in projection first and then checking a velocity concordance criterion, we identify them directly in redshift space using Hickson-like criteria. The methodology was tested on a mock lightcone of galaxies built from the outputs of a recent semi-analytic model … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 46 publications
(83 reference statements)
0
39
0
Order By: Relevance
“…Recently, Díaz-Giménez et al (2018) combined the advantages of above two selection algorithms and applied their new algorithm on the galaxy catalogue of SDSS-DR12 (Alam et al 2015). In specific, they first apply a redshift filter to remove the background galaxies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Díaz-Giménez et al (2018) combined the advantages of above two selection algorithms and applied their new algorithm on the galaxy catalogue of SDSS-DR12 (Alam et al 2015). In specific, they first apply a redshift filter to remove the background galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…They also applied the similar richness and compactness criteria as used byMcConnachie et al (2008), but the isolation criterion was not taken into account.3. HMCG: As we already mentioned,Díaz-Giménez et al (2018) applied a redshift filter on galaxy sample before starting the Hickson's criteria to search CGs, where a sample of 462 CGs are finally extracted from the SDSS-DR12.…”
mentioning
confidence: 99%
“…Moreover, DGM10 found that the frequency (space density) of CGs was roughly 10 times higher in the simulations than observed, suggesting that the HCG sample was 90 per cent incomplete, mainly in groups dominated by a single galaxy (as previously noted by Prandoni et al 1994). In subsequent studies by our team (Díaz-Giménez et al 2012;Díaz-Giménez & Zandivarez 2015;Taverna et al 2016;Díaz-Giménez et al 2018), CGs were extracted from the public outputs of different SAMs based on different physics or from those of older SAMs run on the dark matter haloes extracted from cosmological simulations run with different cosmological parameters. These studies led to different fractions of physically dense groups.…”
Section: Introductionmentioning
confidence: 50%
“…Absolute magnitudes were interpolated between different snapshots. Since the SAMs provide the galaxy absolute magnitudes, to compute the observer-frame apparent magnitudes it is necessary to include a k-decorrection procedure, which was done following the recipes described in Díaz-Giménez et al (2018).…”
Section: Mock Galaxy Lightconesmentioning
confidence: 99%
See 1 more Smart Citation